Global governance of financial systems : the international regulation of systemic risk - Alexander, Kern, 1962- (Finance and the economy., 2006)
The authors set forth the economic rationale for international financial regulation & what role, if any, international regulation can play in effectively managing the systemic risk while providing accountability to all affected nations.